Pengaruh berbagai Larutan Abu dan Natrium Hidroksida terhadap Pencernaan Bahan Serat Limbah Industri Tanaman Perkebunan - Dwierra E. Amirroenas; Toha Sutardi; Nur Aeni Sigit (Buletin Ilmu Makanan Ternak, 1990)
Alkalinity of saturated solutions of some ashes were compared with that of 5% NaOH(pH=13.0)and 25% limestone (pH=12.2).The pH of the ash solution made of 17 % palm cluster was 11.5, that of 25% palm fibre was 10.7, that of 10% rice hulls was 7.9, and that of 10% sugarcane by product was 6.4. The solutions were then sprayed on sugarcane tops, sugarcane bagasse, palm fiber, cocoa seed coat, cocoa shell, rice straw, and Napier grass at a dose of 0.05 or 1.0 ml/kg dry matter. Effectiveness of the solutions in improving the in vitro digestibility was close correlated with pH. The 5% NaOH appeared to be the most effective in improving the in vitro digestibility, followed by limestone and then palm fiber. The most prominent changed in digestibility was occured in low quality roghages such as palm fiber, rice straw, and sugarcane bagasse. The 0.5 ml/g of the 5% NaOH solution increased the in vitro dry matter digestibility (IVDMD) of palm fiber by 45.24% and of the in vitro organic matter digestibility (IVOMD) by 48.49%. The treated roughages were then mixed into isonitrogenous (crude protein 13 - 14 %) and isolaric (gross energy 3.5 - 3.9 Mcal/kg) rations. Rate of disappearance of dry matter and organic matter of the tested rations were faster than that of the commercial concentrate-Napier grass diet. The 5% NaOH solutions was the most effective in increasing the rate of disapearances. It was concluded that the effectiveness of the ash solutions as alkali sources in improving digestibility of low quality roughages was limited by their low alkalinity.